Canadian dental hygienists' experiences and perceptions of regulatory guidelines during the COVID-19 pandemic: a qualitative descriptive analysis - Lindsay K. Macdonald; Michael Glogauer; Paul Allison; Carlos Quiñonez; Sreenath Madathil; Leigha D. Rock (BMC, 2022)
Abstract Background In Spring of 2020, due to the COVID-19 pandemic, Canadian provincial dental hygiene regulatory bodies implemented new practice guidelines. Reports of stress, anxiety and conflict experienced by dental hygienists have been linked to miscommunication between oral health regulators at this time. Limited data exists on the perceptions and experiences of dental hygienists navigating new guidelines for dental hygiene care during the pandemic. Therefore, the objective of our study was to explore via descriptive thematic analysis how dental hygienists experienced and perceived: i) dental hygiene practice during the COVID-19 pandemic, and ii) their regulatory body's COVID-19 guidelines. Methods Participants were identified through provincial dental hygiene licensing bodies. Online bi-monthly questionnaires were administered to participants (n = 876) from December 2021 to January 2022. Two open-ended questions were asked in the questionnaire. A qualitative descriptive thematic analysis was applied to these two questions. Results Major themes at baseline relayed challenges related to workplace compliance, patient treatment and communication of practice protocols. Across responses, hygienists confirmed conflicting messaging from regulators and guideline interpretations as stressors impacting their professional practice and satisfaction within the profession. Participant responses at endpoint cited increased satisfaction with regulatory guidelines as the pandemic evolved, yet inconsistencies in regulators' messaging was noted as a prevailing issue. Conclusion Inconsistent guideline messaging reflects an increased need for collaboration amongst oral health care regulators to streamline protocols for practice and reduce interprofessional conflict in pandemic circumstances. A national unified approach is warranted in establishing guidelines for dental hygiene practice in Canada.